2001
DOI: 10.1016/s1534-5807(01)00084-3
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial, an Intracellular Adaptor Protein, Is Required for Myoblast Fusion in Drosophila

Abstract: Somatic muscle formation in Drosophila requires fusion of muscle founder cells with fusion-competent myoblasts. In a genetic screen for genes that control muscle development, we identified antisocial (ants), a gene that encodes an ankyrin repeat-, TPR repeat-, and RING finger-containing protein, required for myoblast fusion. In ants mutant embryos, founder cells and fusion-competent myoblasts are properly specified and patterned, but they are unable to form myotubes. ANTS, which is expressed specifically in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
180
2
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(190 citation statements)
references
References 33 publications
(2 reference statements)
6
180
2
2
Order By: Relevance
“…The insertion site of the EP vector within canB2 was determined by generating a genomic PCR product by using primers from canB2 intron 1 and the EP DNA, followed by cloning of the 258-bp fragment into the TOPO pCRII vector (Invitrogen) and sequencing. canB2 180 ͞CyO-GFP arm (14) was obtained from K. Sullivan (University of California, Berkeley), and MHC-GFP stocks were established as described in Chen and Olson (16). To generate UAS-mcanA act lines, a murine canA␣ cDNA encoding amino acids 1-398 was cloned into the pUAST P element vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The insertion site of the EP vector within canB2 was determined by generating a genomic PCR product by using primers from canB2 intron 1 and the EP DNA, followed by cloning of the 258-bp fragment into the TOPO pCRII vector (Invitrogen) and sequencing. canB2 180 ͞CyO-GFP arm (14) was obtained from K. Sullivan (University of California, Berkeley), and MHC-GFP stocks were established as described in Chen and Olson (16). To generate UAS-mcanA act lines, a murine canA␣ cDNA encoding amino acids 1-398 was cloned into the pUAST P element vector.…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate phenotypic analyses, EP(2)0774, MHC-GFP was balanced over CyO, GFP-Actin. This combination allows for the easy identification of homozygous EP(2)0774, MHC-GFP larvae because the MHC-GFP transgene expresses strongly in body wall muscles (16), whereas GFP-Actin generates a fluorescent signal in portions of the gut.…”
Section: Methodsmentioning
confidence: 99%
“…The cytoplasmatic tails of the adhesion molecules are most likely to be involved in this signal transduction process (Sink, 2006). For example, the intracellular domain of Duf/Kirre is needed to recruit the multidomain protein Rolling Pebbles 7 (Rols7), also known as Antisocial (Ants) (Chen and Olson, 2001;Menon and Chia, 2001). This leads to colocalization of Rols and Duf/Kirre in a ring-like manner within the FuRMAS in the fc/ growing myotube (Kesper et al, 2007).…”
Section: Establishment and Known Components Of The Furmasmentioning
confidence: 99%
“…Immunoprecipitaion (CoIPs) studies with Duf and Rols/Ants or Rols and Mbc after transfection into S2 cells revealed interaction of Rols/Ants with Duf as well as with Mbc (Chen and Olson, 2001). Thus, Rols7/Ants might Fig.…”
Section: Establishment and Known Components Of The Furmasmentioning
confidence: 99%
“…Dumbfounded/Kin-of-IrreC and Roughest/Irregular-optic-chiasma-C are expressed on the founder myoblasts and associate with Stick and Stones and Hibris found at the surface of fusion-competent myoblasts to trigger intracellular signaling cascades leading to fusion (4)(5)(6)(7). The signaling intermediates include scaffold proteins (ELMO, Blown Fuse, Antisocial) (8)(9)(10), kinase (p21-activated kinase) (11), guanine nucleotide exchange factors (GEFs) [Myoblast City (MBC), Loner] (12, 13), GTPase (Rac), (14) and actin nucleation regulators (Kette, WAVE, WASP, WASP-interacting protein) (15)(16)(17)(18)(19). Some of these proteins ultimately promote the formation of actin-driven podosome-like structures in the fusion-competent cells that invade founder cells for membrane fusion (20,21).…”
mentioning
confidence: 99%